An Update on the Surgical Management of the Bulbous and Boxy Tip. Issue 1 (21st December 2021) - Rohrich, Rod J.; Avashia, Yash J.; Savetsky, Ira L.
Abstract : Summary: The bulbous and box tips are two common morphologies encountered in rhinoplasty. Nasal tip reshaping is a challenging aspect of rhinoplasty. Understanding the classifications of nasal tip morphologies aids when performing a nasal-facial analysis. The management algorithm for both tip morphologies shares various techniques. These techniques include but are not limited to cephalic trim, transdomal sutures, and interdomal sutures. A graduated approach to managing the variations in bulbous and boxy tips will help in achieving consistent results. New concepts applied to the management include supporting alar rims with alar contour grafts, closing dead space through a series of techniques, and managing the soft-tissue envelope, which is often in excess.